2012
DOI: 10.1016/j.pain.2012.03.024
|View full text |Cite
|
Sign up to set email alerts
|

Antinociceptive effect of peripheral serotonin 5-HT2B receptor activation on neuropathic pain

Abstract: -nociceptive effect of peripheral serotonin 5-HT2B receptor activation on neuropathic pain.. PAIN, Elsevier, 2012, 153 (6), pp.1320-31. <10.1016/j.pain.2012.03.024>. 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 receptor. CCI resulted in a biphasic upregulation of 5-HT 2B receptor expression in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 73 publications
(64 reference statements)
3
18
0
Order By: Relevance
“…To examine the role of DRG MZF1 in the development of CCI-induced neuropathic pain, we carried out the CCI model on day 7 post-injection. Consistent with previous studies [3;38], CCI led to long-term mechanical, thermal, and cold pain hypersensitivities on the ipsilateral side in the vehicle-injected rats (n = 8 rats). The paw withdrawal thresholds in response to mechanical stimuli applied to the ipsilateral hind paw were significantly reduced as compared to pre-injury baseline values, a behavioral indication of mechanical pain hypersensitivity (Fig.…”
Section: Resultssupporting
confidence: 92%
“…To examine the role of DRG MZF1 in the development of CCI-induced neuropathic pain, we carried out the CCI model on day 7 post-injection. Consistent with previous studies [3;38], CCI led to long-term mechanical, thermal, and cold pain hypersensitivities on the ipsilateral side in the vehicle-injected rats (n = 8 rats). The paw withdrawal thresholds in response to mechanical stimuli applied to the ipsilateral hind paw were significantly reduced as compared to pre-injury baseline values, a behavioral indication of mechanical pain hypersensitivity (Fig.…”
Section: Resultssupporting
confidence: 92%
“…Our results concur with published studies indicating that administration of the 5‐HT 2B receptor antagonist SB‐204741 diminishes thermal and mechanical allodynia as well as C‐fiber‐evoked potentials in neuropathic rats [Aira et al, , , , ]. In contrast, it has been shown that intrathecal injection of BW723C86 (a 5‐HT 2B/2C receptor agonist) attenuates mechanical and cold allodynia induced by chronic constriction injury and this effect is prevented by coinjection with the 5‐HT 2B receptor antagonist RS‐127445 [Urtikova et al, ] suggesting an antinociceptive role for the spinal 5‐HT 2B receptors. This discrepancy could be due to the neuropathic model or the dose and selectivity of BW723C86.…”
Section: Discussionsupporting
confidence: 92%
“…These data suggest a pronociceptive role for the spinal 5‐HT 2B receptors in neuropathic pain. In contrast, a recent study showed that intrathecal injection of BW723C86 significantly attenuates mechanical and cold allodynia and these effects are prevented by the 5‐HT 2B receptor antagonist, RS‐127445 [Urtikova et al, ] suggesting an antinociceptive role for this receptor. Thus, the purpose of this study was to investigate the role of spinal 5‐HT 2B receptors in the maintenance of neuropathic pain using selective and high‐affinity 5‐HT 2B receptor antagonists such as LY‐266097, which has not been examined before, and RS‐127445 [Audia et al, ; Bonhaus et al, ].…”
Section: Introductionmentioning
confidence: 98%
“…However, although selective serotonin reuptake inhibitors are among the most prescribed medications for CNP, little efficacy has been shown in clinical pain trials (Vranken, 2009; Urtikova et al, 2012). While initial behavioral experiments suggested an anti-nociceptive role for serotonin, the link between the neurotransmitter and pain is now viewed as more complex and serotonin may have both pro- and anti-nociceptive properties, depending on the location and mechanism of release (central from raphe vs. peripheral from mast cells) and the serotonergic receptors involved (Urtikova et al, 2012; Bobinski et al, 2015). …”
Section: Discussionmentioning
confidence: 99%